Chypre: Un Enjeu Prépondérant de L’équilibre Géopolitique et Géostratégique Est-Méditerranéen - MIRANTE-PSALTAKIS, Fotini Katy (Études helléniques / Hellenic Studies, 2011)
Cyprus: a divided country, militarized, continuously coveted, pivotal, having a key geostrategic and geoeconomic role now, but, above all, an island marked by a singular history, a rupture that of 1974, as well as a permanent conflictuality, immutable... A space where power relations, strategies of power and the recurrence of power struggles help to maintain a geopolitical balance particularly volatile and subject to latent tensions, stubborn resentments related to a complex reality after all requiring a certain humility.